2020
DOI: 10.3390/jcm9051445
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hyperglycemia on Dexmedetomidine-Induced Cardioprotection in the Isolated Perfused Rat Heart

Abstract: Pharmacological preconditioning (PC) and postconditioning (PoC), for example, by treatment with the α2-adrenoreceptor agonist Dexmedetomidine (Dex), protects hearts from ischemia-reperfusion (I/R) injury in experimental studies, however, translation into the clinical setting has been challenging. Acute hyperglycemia adversely affects the outcome of patients with myocardial infarction. Additionally, it also blocks cardioprotection by multiple pharmacological agents. Therefore, we investigated the possible influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 57 publications
1
19
0
2
Order By: Relevance
“…The isolated hearts were mounted on the Langendorff system and perfused with perfused with Kreb's Henseleit solution at 37°C. The inflow of physiological solution was stopped for 30 minutes to induce global ischemia and afterwards, the flow of KH was reinstituted for 120 minutes to establish reperfusion 18 , 19 .…”
Section: Methodsmentioning
confidence: 99%
“…The isolated hearts were mounted on the Langendorff system and perfused with perfused with Kreb's Henseleit solution at 37°C. The inflow of physiological solution was stopped for 30 minutes to induce global ischemia and afterwards, the flow of KH was reinstituted for 120 minutes to establish reperfusion 18 , 19 .…”
Section: Methodsmentioning
confidence: 99%
“…The respective Mannitol concentration of 11 mmol/L employed in this study was taken from the literature as well as one of our previous studies. In a preliminary experimental protocol, we investigated the influence of hyperglycemia on cardioprotection by Dexmedetomidine [ 42 ]. To ensure comparable osmolarity in all experiments, normoglycemic groups were treated with Mannitol—achieving the same osmolar conditions to hyperglycemia without affecting glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed on male Wistar rats (2–3 months old), as described previously [ 42 ]. In short, animals were anesthetized with intraperitoneal injection of pentobarbital (80 mg/kg body weight, Narcoren, Merial, Germany) and decapitated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with these results, our own research showed that preconditioning with dexmedetomidine confers cardioprotection despite the presence of acute hyperglycemia. Unfortunately, elevated glucose levels interfere with dexmedetomidine-induced postconditioning [ 90 ]. Additionally, in hearts with endothelial dysfunction, the protective effects of dexmedetomidine preconditioning are maintained [ 91 ].…”
Section: Alpha-2 Agonistsmentioning
confidence: 99%